Web Monitoring the Potential of Solar Power Plants Based on the Internet of Things - Abdillah Hartawan; Afandi A.N.; Haris Abdul; Zinul Falah Moh.; Baihaqi Mas Ahmad; Sujito (E3S Web of Conferences, 2024)
The market for renewable energy is expanding quickly to support power production, where solar energy is widely used and developed in applied technologies significantly. When assessing solar energy potential, one must consider natural energy resources based on the wind speed. As a result, the systems covered by this work feature two monitoring modes: on-site monitoring using a monitoring module and smartphone applications applied to the method, which can download data for Android smartphones or desktop computers. Technically, data monitoring is uploaded to a cloud database regularly through data updates for monitoring devices automatically that obtain and present the most recent information. Research indicates that solar radiation directly impacts electrical voltage, as it is precisely proportionate to the intensity of sunshine. In testing conducted from 07.00 to 17.00 WIB, the lowest solar panel output voltage of 20.4 V with a current of 0.2 A was obtained. The most outstanding result is at 12.00 WIB with a point of 23.59 V and 0.7 A. The study also demonstrates how the surrounding temperature influences the amount of electrical energy generated.